Inflammatory Conditions Dictate the Effect of Mesenchymal Stem or Stromal Cells on B Cell Function - Luk, Franka; Carreras-Planella, Laura; Korevaar, Sander S.; de Witte, Samantha F. H.; Borràs, Francesc E.; Betjes, Michiel G. H.; Baan, Carla C.; Hoogduijn, Martin J.; Franquesa, Marcella (Frontiers in Immunology, 2017)
The immunomodulatory capacity of mesenchymal stem or stromal cells (MSC) makes them a promising tool for treatment of immune disease and organ transplantation. The effects of MSC on B cells are characterized by an abrogation of plasmablast formation and induction of regulatory B cells (Bregs). It is however unknown how MSC interact with B cells under inflammatory conditions. In the present study, adipose tissue-derived MSC were pre-treated with 50 ng/ml IFN-γ for 96h (MSC-IFN-γ) to simulate inflammatory conditions. Mature B cells were obtained from spleens by CD43-selection. B cells were co-cultured with MSC and stimulated with anti-IgM, anti-CD40 and IL-2 and after 7 days B cell proliferation, phenotype, IgG and IL-10 production were analyzed. MSC did not inhibit B cell proliferation but increased the percentage of CD38hi CD24hi B cells (Bregs) and IL-10 production, while MSC-IFN-y significantly reduced B cell proliferation and inhibited IgG production by B cells in a more potent fashion but did not induce Bregs or IL-10 production. Both MSC and MSC-IFN-y required proximity to target cells and being metabolically active to exert their effects. Indoleamine 2,3 dioxygenase (IDO) expression was highly induced in MSC-IFN-y and was responsible of the anti-proliferative and Breg reduction since addition of tryptophan (TRP) restored MSC properties. Immunological conditions dictate the effect of MSC on B cell function. Under immunological quiescent conditions MSC stimulate Breg induction, whereas under inflammatory conditions MSC inhibit B cell proliferation and maturation through depletion of TRP. This knowledge is useful for customizing MSC therapy for specific purposes by appropriate pre-treatment of MSC.